2020
DOI: 10.3892/or.2020.7758
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA NOX4 promotes the development of colorectal cancer via the microRNA‑485‑5p/CKS1B axis

Abstract: Colorectal cancer (CRC) is a common malignancy globally. The aim of the present study was to explore the role and the working mechanism of circular RNA NADPH oxidase 4 (circNOX4; circBase ID, hsa_circ_0023990) in CRC. Reverse transcription-quantitative (RT-q)PCR was used to examine the expression of circNOX4, NOX4 mRNA and microRNA (miR)-485-5p in CRC tissues and cell lines. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and Transwell assays were performed to analyze CRC cell viability and motili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Liu et al disclosed that miR‐485‐5p restrained CRC cell proliferation and motility as well as stimulated apoptosis through circAPLP2/miR‐485‐5p/FOXK1 regulatory axis 18 . Wang et al demonstrated the inhibitory effects of miR‐485‐5p on CRC by circNOX4/miR‐485‐5p/CKS1B axis 41 . In line with these findings, we found that miR‐485‐5p elevation caused a remarkable suppression in CRC cell colony formation and motility and a distinct enhancement in cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al disclosed that miR‐485‐5p restrained CRC cell proliferation and motility as well as stimulated apoptosis through circAPLP2/miR‐485‐5p/FOXK1 regulatory axis 18 . Wang et al demonstrated the inhibitory effects of miR‐485‐5p on CRC by circNOX4/miR‐485‐5p/CKS1B axis 41 . In line with these findings, we found that miR‐485‐5p elevation caused a remarkable suppression in CRC cell colony formation and motility and a distinct enhancement in cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported CKS1B in breast cancer was associated with patient's age, estrogen, and progesterone receptor levels and increased with malignant degree [ 15 ]. Besides, CKS1B was also found to be upregulated in patients with prostate cancer, colorectal cancer, leukemia, retinoblastoma, and other malignant diseases or animal models [ 10 , 28 , 29 ]. Therefore, CKS1B is generally regarded as a cancer-promoting factor.…”
Section: Discussionmentioning
confidence: 99%
“…MTT assay was conducted as previously described [ 21 ]. In brief, a total of 20 μL of 5% MTT reagent (SenBeJia Biological Technology, Jiangsu, China) was incubated with CSCC cells for 4 h. The formazan products were dissolved with 100 μL of dimethyl sulfoxide (DMSO; Sangon Biotech, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Transwell invasion assay was conducted as previously described [ 21 ]. The diluted Matrigel (50 μL/well; BD Biosciences, San Jose, CA, USA) was added to the upper compartments.…”
Section: Methodsmentioning
confidence: 99%